Understanding foliar accumulation of atmospheric Hg in terrestrial vegetation: Progress and challenges. Issue 24 (28th September 2022) - Liu, Yanwei; Liu, Guangliang; Wang, Zhangwei; Guo, Yingying; Yin, Yongguang; Zhang, Xiaoshan; Cai, Yong; Jiang, Guibin
Abstract: Foliar accumulation of atmospheric mercury (Hg), particularly gaseous elemental mercury (Hg(0)), accounts for a significant amount of atmospheric Hg deposition and influences the Hg geochemical cycle. Foliar Hg accumulation occurs as the net result of uptake, adsorption, fixation, re-emission, and other processes. The combination of these processes influences foliar Hg speciation, translocation, toxicity, transport, and bioavailability, which eventually affects the environmental risk of Hg. Therefore, a systematic understanding of the various processes involved in foliar Hg accumulation is urgently needed. This review summarizes the current knowledge, research progress, and remaining knowledge gaps regarding foliar Hg accumulation processes and the biochemical mechanisms involved. Atmospheric Hg is biochemically fixed within foliage after stomatal and/or nonstomatal uptake, with foliar Hg then volatilized after reduction, washed off via throughfall, deposited on soil surfaces via litterfall or stored within vegetation over time. Mechanisms underlying these processes and future perspectives on foliar accumulation are hereby discussed with the aim of reducing knowledge gaps on foliar Hg accumulation. The combination of different methods, such as Hg speciation analysis, isotope tracer techniques, element imaging, biological technologies, and ecologically microcosmic methods, will help clarify Hg speciation, transformation, and subcellular distribution in foliage, and quantitate different Hg fluxes during foliar Hg accumulation and litterfall decomposition. Measurements and modeling on the foliar accumulation process of atmospheric Hg under natural and human perturbations are also essential. These future investigations will help comprehensively understand the processes influencing atmospheric Hg interactions with foliage and evaluate the environmental fates and risks of foliar Hg. Abstract : UF0001